2013
DOI: 10.1242/bio.20134804
|View full text |Cite
|
Sign up to set email alerts
|

Altered biometal homeostasis is associated with CLN6 mRNA loss in mouse neuronal ceroid lipofuscinosis

Abstract: SummaryNeuronal ceroid lipofuscinoses, the most common fatal childhood neurodegenerative illnesses, share many features with more prevalent neurodegenerative diseases. Neuronal ceroid lipofuscinoses are caused by mutations in CLN genes. CLN6 encodes a transmembrane endoplasmic reticulum protein with no known function. We characterized the behavioural phenotype of spontaneous mutant mice modeling CLN6 disease, and demonstrate progressive motor and visual decline and reduced lifespan in these mice, consistent wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
47
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(52 citation statements)
references
References 48 publications
5
47
0
Order By: Relevance
“…Early studies showed that higher levels of expressed mutant SOD1 correlate with more rapid onset and progression of disease symptoms in the ALS model mice (Gurney et al, 1994;Wong et al, 1995;Dal Canto and Gurney, 1997). This correlation is substantiated by delayed symptoms in ALS mice due to decreased mutant SOD1 levels (Ralph et al, 2005;Urushitani et al, 2007;Henriques et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Early studies showed that higher levels of expressed mutant SOD1 correlate with more rapid onset and progression of disease symptoms in the ALS model mice (Gurney et al, 1994;Wong et al, 1995;Dal Canto and Gurney, 1997). This correlation is substantiated by delayed symptoms in ALS mice due to decreased mutant SOD1 levels (Ralph et al, 2005;Urushitani et al, 2007;Henriques et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Underscoring this, transgenic mice overexpressing mutant SOD1 develop an ALS-like phenotype that is proportional to the expression level of the mutant SOD1. Higher levels of mutant SOD1 cause earlier disease onset, more severe disease symptoms, and more rapid disease progression (Gurney et al, 1994;Wong et al, 1995;Henriques et al, 2010). However, despite the clear link between motor neuron death and disease symptoms in SOD1-associated forms of ALS, the fundamental basis of SOD1 toxicity in ALS is not fully understood.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, Zn 2ϩ homeostasis is a major focus of current research in other forms of NCL and NCL-Parkinsonism overlap disorders, caused by CLN6 mutation and ATP13A2 mutation, respectively (52)(53)(54). In CLN6 disease models, a major disturbance in intracellular Zn 2ϩ regulation and Ca 2ϩ regulation have been identified (55,56). To date, there is no compelling evidence that CLN3 itself functions as an ion transporter, but this possibility cannot yet be ruled out.…”
Section: Discussionmentioning
confidence: 99%
“…Lysosomes have been shown to act as a zinc sink, ameliorating toxicity by absorbing excess zinc from the cytosol (Kukic et al, 2013). This process requires lysosome acidification and subsequent exocytosis (Kukic et al, 2014) and can lower toxic cytosolic zinc concentrations in disease states such as neuronal ceroid lipofuscinoses (NCLs, Kanninen et al, 2013) and breast cancer (Lopez et al, 2011). Drosophila CATSUP is the homologue of human Zip7 which has been shown to release zinc from the ER and Golgi (Huang et al, 2005, Taylor et al, 2004.…”
Section: Regulation Of Zinc Homeostasis In Multicellular Organisms Ismentioning
confidence: 99%